Inovasi Buku Matematika Berpendekatan Realistic Mathematics Education Terintegrasi Nilai Keislaman pada Materi Bilangan - Aeni Nur Taskiyah; Putri Nur Malasari (Institut Agama Islam Negeri Curup, 2022)
Mathematics books based on Realistic Mathematics Education (RME) integrated with Islamic values will make mathematics learning more memorable. The reason is, that the books or learning resources used by most students only contain a collection of material and practice questions. In addition, from the factor of students, many still do not understand the material because the examples given are not realistic. The purpose of this study is to determine the feasibility and practicality of mathematics books based on RME integrated Islamic values in grade 7 number material. This study uses the RnD type with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data collection instruments were interviews, validation sheets, and questionnaires. The population of this study was students of MTs Al-Ma'arif Gembong Pati. The sample is 7th-grade students of MTs Al-Ma'arif Gembong Pati which was taken through the purposive sampling technique. This math book was tested for feasibility by a team of experts consisting of 2 material experts, 2 media experts, and 2 religious experts. In the feasibility test, the material expert got an average score of 115 with very decent criteria. The media expert obtained an average score of 125.5 with very decent criteria. And religious experts get an average score of 64.5 with very decent criteria. Then, to find out the practicality of the book, product trials were carried out in small and large groups. Small groups consisting of 10 students obtained an average score of 66.6 with very practical criteria. A large group followed by 42 students got an average score of 65.9 with very practical criteria. So it can be concluded that the RME-based mathematics book integrated Islamic values in grade 7 number material is feasible and practical to be used in learning mathematics.